2021
DOI: 10.1021/acsomega.0c05781
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of SARS-CoV-2 Virus Using Dual Reverse Transcriptional Colorimetric Loop-Mediated Isothermal Amplification

Abstract: The outbreak and pandemic of COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has developed into a public health emergency of international concern. The rapid and accurate detection of the virus is a critical means to prevent and control the disease. Herein, we provide a novel, rapid, and simple approach, named dual reverse transcriptional colorimetric loop-mediated isothermal amplification (dRT-cLAMP) assay, to accelerate the detection of the SARS-CoV-2 virus without using exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…3B ). All results indicated that the triplex primer combination of the set3, set1, and set5 (S3+S1+S5) exhibited the best performance and was therefore selected as the optimal LAMP primer combination for further studies ( Ji et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B ). All results indicated that the triplex primer combination of the set3, set1, and set5 (S3+S1+S5) exhibited the best performance and was therefore selected as the optimal LAMP primer combination for further studies ( Ji et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 constantly changes through genetic mutations, with novel variants of concern (VOC) occurring over time, such as Alpha, Beta, Gamma, Delta and Omicron, which are more transmissible, more pathogenic, or have better capability for immune escape ( Hacisuleyman et al, 2021 ; Hoffmann et al, 2021 ; Wang et al, 2021 ). All of these VOCs and some other genomic mutations make it difficult to detect SARS-CoV-2 with only one single target ( Ji et al, 2021 ; Mohon et al, 2020 ). Therefore, LAMP primer sets targeting different SARS-CoV-2 regions may provide more accurate diagnosis results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The color change can be observed with the naked eye, even at low concentrations of the target analyte. Simultaneously, colorimetric biosensors have been used in POC for their advantages of direct readout, convenient operation, low instruments requirements, and portability [ 61 , 62 , 63 ]. In recent years, a series of smart materials that can induce color changes have been developed using noble metals, metal oxides, and carbon materials [ 64 , 65 ].…”
Section: Colorimetric Biosensors For Sars-cov-2 Detectionmentioning
confidence: 99%
“…比色法(Colorimetry)是指利用检测设备中可视化的 颜色变化, 反映相关生物化学信号的一种方法, 可以借 助荧光分子、纳米金颗粒等标记探针, 直观地检测病 毒 [70][71] 、蛋白质 [72] 等生物标志物. 比色法的方式有很多, RT-PCR 作为目前 SARS-CoV-2 的核心检测方法, 正是 比色法的一种.…”
Section: 比色法unclassified